Clinical pathological characteristics of pelvic bone tumors - Starčević, Darko; Simic, Ljubica; Djuricic, Goran; Rajakovic, Stanislav; Sopta, Jelena (Medicinski podmladak, 2021)
Introduction: Bone tumors are rare neoplasms whose therapy depends on the location. Pelvic bones represent a special anatomical whole, diagnosis and therapy of pelvic tumors in addition to the pathohistological type largely depends on the anatomical specifics of that region.Aim: The aim of this study was to show the frequency, as well as clinical and pathological characteristics of primary and secondary tumors of the pelvis.Material and methods: The research as a descriptive study in the period from January 1,  to December 31, 2019 at the Institute of Pathology of the Medical Faculty of the University of Belgrade and includes 33 patients. Demographic, clinical and radiological data were obtained from the Bone Tumor Registry. Statistical processing and analysis were done in the Statistical Package for Social Science SPSS Windows version 22. (IBM Chicago, Ilinois, USA).Results: Of the 33 patients, 55% had secondary pelvic tumors, primarily cancer metastases (37%). In 21% of cases, primary malignant bone was diagnosed, and in 12%, primary benign bone tumor. Hematopoietic neoplasms were verified in 12%.Conclusion: Pelvic bone tumors are not common, but of great importance are these neoplasms, in orthopedic oncology, represents their malignant biological behavior. The most common primary malignant tumor in adults is chondrosarcoma, and in children Ewing sarcoma. Lung cancer with they metastasize to the pelvic bones with the highest frequency. Plasmacytoma in adults, Langerhans cellular histiocytosis are hematological neoplasms seen at this site.Key words: Pelvis, Bone, Tumor, metastases, chondrosarcoma
Keywords: Pelvis, Bone, Tumor, metastases, chondrosarcoma